SOSIALISASI DAN PENANAMAN MANGROVE SEBAGAI UPAYA PERBAIKAN LINGKUNGAN DAN PENCEGAHAN ABRASI DI DESA PEUNAGA CUT UJONG - Yusuf, Alfisyahrin; Masrura, Delfian; Hasdanita, Fitry; Kasaf, Michel; Arief Diana, Muhammad; Rizqi Maysyarah Hadi, Tjut; Lisdayanti, Eka; Rahmawati; Yunisa Fahmi, Nadya; Najmi, Nurul (Fakultas Teknik, Universitas Samudra, 2025)
This community service initiative aims to enhance awareness and encourage active participation among the residents of Peunaga Cut Ujong Village, Meureubo Subdistrict, West Aceh Regency, in environmental conservation efforts through mangrove planting. Located in a coastal area vulnerable to erosion and exposed to air pollution due to coal-burning activities, this village faces significant environmental challenges. Employing an educational and participatory approach, the program involved raising awareness about the ecological functions of mangroves and conducting direct planting activities in a mangrove forest area approximately 100 meters from the shoreline. The outcomes of the initiative indicated a positive response from the community, demonstrated by increased environmental awareness and active involvement in conservation efforts. Mangrove planting is expected to function as a coastal protection barrier, an air pollutant absorber, and a potential site for ecotourism and aquaculture development. This initiative highlights the importance of synergy between academia, the local community, and the industrial sector in creating sustainable environmental solutions. Continuous evaluation and the replication of similar programs are strongly recommended to enhance their long-term impact.